Persistent Contamination of Octopuses and Mussels with Lipophilic Shellfish Toxins during Spring Dinophysis Blooms in a Subtropical Estuary - Mafra, Luiz L. (Mar Drugs, 2015)
This study investigates the occurrence of diarrhetic shellfish toxins (DSTs) and their producing phytoplankton species in southern Brazil, as well as the potential for toxin accumulation in co-occurring mussels (Perna perna) and octopuses (Octopus vulgaris). During the spring in 2012 and 2013, cells of Dinophysis acuminata complex were always present, sometimes at relatively high abundances (max. 1143 cells L(−1)), likely the main source of okadaic acid (OA) in the plankton (max. 34 ng L(−1)). Dinophysis caudata occurred at lower cell densities in 2013 when the lipophilic toxins pectenotoxin-2 (PTX-2) and PTX-2 seco acid were detected in plankton and mussel samples. Here, we report for the first time the accumulation of DSTs in octopuses, probably linked to the consumption of contaminated bivalves. Perna perna mussels were consistently contaminated with different DSTs (max. 42 µg kg(−1)), and all octopuses analyzed (n = 5) accumulated OA in different organs/tissues: digestive glands (DGs) > arms > gills > kidneys > stomach + intestine. Additionally, similar concentrations of 7-O-palmytoyl OA and 7-O-palmytoly dinophysistoxin-1 (DTX-1) were frequently detected in the hepatopancreas of P. perna and DGs of O. vulgaris. Therefore, octopuses can be considered a potential vector of DSTs to both humans and top predators such as marine mammals.